Low-pass whole-genome sequencing in clinical cytogenetics: a validated approach - Dong, Zirui; Zhang, Jun; Hu, Ping; Chen, Haixiao; Xu, Jinjin; Tian, Qi; Meng, Lu; Ye, Yanchou; Wang, Jun; Zhang, Meiyan; Li, Yun; Wang, Huilin; et al. (Genetics in medicine, 2016)
Purpose: Chromosomal microarray analysis is the gold standard for copy-number variant (CNV) detection in prenatal and postnatal diagnosis. We aimed to determine whether next-generation sequencing (NGS) technology could be an alternative method for CNV detection in routine clinical application. Methods: Genome-wide CNV analysis (>50 kb) was performed on a multicenter group of 570 patients using a low-coverage whole-genome sequencing pipeline. These samples were referred for chromosomal analysis; CNVs (i.e., pathogenic CNVs, pCNVs) were classified according to the American College of Medical Genetics and Genomics guidelines. Results: Overall, a total of 198 abortuses, 37 stillbirths, 149 prenatal, and 186 postnatal samples were tested. Our approach yielded results in 549 samples (96.3%). In addition to 119 subjects with aneuploidies, 103 pCNVs (74 losses and 29 gains) were identified in 82 samples, giving diagnostic yields of 53.2% (95% confidence interval: 45.8, 60.5), 14.7% (5.0, 31.1), 28.5% (21.1, 36.6), and 30.1% (23.6, 37.3) in each group, respectively. Mosaicism was observed at a level as low as 25%. Conclusions: Patients with chromosomal diseases or microdeletion/microduplication syndromes were diagnosed using a high-resolution genome-wide method. Our study revealed the potential of NGS to facilitate genetic diagnoses that were not evident in the prenatal and postnatal groups. Genet Med 18 9, 940–948.